The performance of various anthropometric assessment methods for predicting low birth weight in adolescent pregnant women - Denise Cavalcante de Barros; Cláudia Saunders; Marta Maria Antonieta de Souza Santos; Beatriz Della Líbera; Silvana Granado Nogueira da Gama; Maria do Carmo Leal (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To evaluate the performance of various anthropometric evaluation methods for adolescent pregnant women in the prediction of birth weight. Methods: It is a cross-sectional study including 826 adolescent pregnant women. In the pre-pregnancy body mass index (BMI) classification, the recommendations of the World Health Organization were compared with that of the Brazilian Ministry of Health and the Institute of Medicine (IOM) of 1992 and 2006. The gestational weight gain adequacy was evaluated according to the classification of IOM of 1992, of 2006 and of the Brazilian Ministry of Health. The newborns were classified as low birth weight (LBW) or macrosomic. Multinomial logistic regression was used for statistical analysis and sensibility, specificity, accuracy, positive and negative predictive values were calculated. Results: The evaluation, according to the Brazilian Ministry of Health, showed the best prediction for LBW among pregnant women with low weight gain (specificity = 69.5%). The evaluation according to the IOM of 1992 showed the best prediction for macrosomia among pregnant women with high weight gain (specificity = 50.0%). The adequacy of weight gain according to the IOM of 1992 classification showed the best prediction for LBW (OR = 3.84; 95%CI 2.19 - 6.74), followed by the method of the Brazilian Ministry of Health (OR = 2.88, 95%CI 1.73 - 4.79), among pregnant women with low weight gain. Conclusion: It is recommended the adoption of the Brazilian Ministry of Health proposal, associated with BMI cut-offs specific for adolescents as an anthropometric assessment method for adolescent pregnant women.